Selinexor, daratumumab, and dexamethasone in patients with relapsed or refractory multiple myeloma. Issue 1 (8th November 2020) - Gasparetto, Cristina; Lentzsch, Suzanne; Schiller, Gary; Callander, Natalie; Tuchman, Sascha; Chen, Christine; White, Darrell; Kotb, Rami; Sutherland, Heather; Sebag, Michael; Baljevic, Muhamed; Bensinger, William; et al.
Abstract: We assessed the safety, efficacy, maximum tolerated dose (MTD), and the recommended phase 2 dose (RP2D) of selinexor, a first in class oral selective inhibitor of nuclear export (100 mg once weekly [QW] or 60 mg twice weekly), in combination with daratumumab (16 mg/kg per label) and dexamethasone (40 mg QW) (SDd) in patients with relapsed refractory multiple myeloma (RRMM). Thirty‐four patients (median prior therapies, 3 [range, 2‐10]) were enrolled; MM was refractory to proteasome inhibitor (PI) in 85%, immunomodulatory agent (IMiD) in 76%, both in 74%, and daratumumab in 6% of patients. Two dose‐limiting toxicities (DLTs) were reported in the selinexor 60 mg twice‐weekly cohort with no DLTs in the 100 mg QW cohort, making 100 mg QW the MTD and RP2D. Common treatment‐related adverse events included thrombocytopenia (70.6%), nausea (70.6%), fatigue (61.8%), anemia (61.8%), and neutropenia (50.0%). Overall response rate was 73% and median progression‐free survival 12.5 months in daratumumab‐naïve patients. SDd was well tolerated and its promising efficacy suggests that further study of this PI‐ and IMiD‐free regimen in RRMM patients who had at least one prior line of therapy including a PI and an IMiD but whose disease is naïve to daratumumab is warranted.